Population Pharmacokinetics of CC-122 - Cheng Y; Chen J; Pourdehnad M; Zhou S; Li Y (Dove Medical Press, 2021)
Yiming Cheng,1 Jian Chen,2 Michael Pourdehnad,3 Simon Zhou,1 Yan Li1 1Clinical Pharmacology & Pharmacometrics, Bristol Myers Squibb, Summit, NJ, USA; 2Non-Clinical Research & Development, Bristol Myers Squibb, Summit, NJ, USA; 3Early Clinical Development, Bristol Myers Squibb, San Francisco, CA, USACorrespondence: Yan LiClinical Pharmacology & Pharmacometrics, Bristol Myers Squibb, 556 Morris Ave, Summit, NJ, 07901, USATel +1 908-481-6203Email yan.li@bms.comBackground: CC-122 is a cereblon-modulating agent that exerts direct cell-autonomous activity against malignant B cells and immunomodulatory effects. Herein, a population pharmacokinetic (popPK) model of CC-122 was developed and the influence of demographic and disease-related covariates on population pharmacokinetic parameters was assessed based on data from three clinical studies of CC-122 (dose range, 0.5– 15 mg) in healthy subjects and cancer patients.Methods: Nonlinear mixed effects modeling was employed in developing a population pharmacokinetic model of CC-122 based on 298 patients from 3 clinical studies.Results: The PK of CC-122 was adequately described with a two-compartment model with first-order absorption and elimination. Tumor types were found to be significantly correlated with apparent clearance (CL/F) and apparent volume of distribution of the central compartment. Creatinine clearance was identified as a statistically significant covariate of CL/F. Sex and body weight were statistically but not clinically relevant on V2/F.Conclusion: In conclusion, the two-compartment model built can be used to adequately describe the time course of the population pharmacokinetics of CC-122 and should serve as the basis for dose adjustment decision-making of CC-122.Keywords: CC-122, population pharmacokinetics, renal impairment